Evaluation of ascorbic acid content in red and yellow bell pepper (capsicum annuum) in Ecuador - Moran Arzube, Andy Valentín; Veloz Ramos, Génesis Nicole; Pasquel Villa, Lisette Deyanira (Revista Universidad de Guayaquil, 2022)
The consumption of Vitamin C has decreased considerably over the years, constituting a health problem. The objective of the present work was designed to evaluate the ascorbic acid content present in red and yellow bell bell pepper (Capsicum annuum) as one of the solutions to restore losses due to processing and to combat the effects of its deficiency. Bell pepper (Capsicum annuum) is a vegetable sown and consumed in Ecuador because it possesses a diversity of nutrients that are very beneficial for human beings, including vitamin A, vitamin B complex, vitamin C. for effect a preliminary phytochemical screening was performed on the previously dried and pulverized vegetable sample, as described by the procedure, the presence of secondary metabolites such as alkaloids, saponins, phenols, tannins and flavonoids was obtained, the concentration of ascorbic acid in redand yellow bell peppers was quantified in samples collected in the commissary chains of the city of Guayaquil by the method of high performance liquid chromatography coupled with UV detection, from which a higher concentration of ascorbic acid was obtained in the red bell pepper with 166. 10 mg/100g and below the yellow bell bell pepper with a concentration of 125.80 mg/100g.
Keywords: Ascorbic acid; (capsicum annuum); Quantify; preliminary phytochemical screening; HPLC UV